Living wage laws: how much do (can) they matter? - Harry J. Holzer (Institute for the Study of Labor (IZA), 2008)
In this paper I review what we have learned about living wage laws and their impacts on the wages, employment and poverty rates of low-wage workers. I review the characteristics of these laws and where they have been implemented to date, and what economic theory tells us about their likely effects in more and less competitive labor markets. I then review two bodies of empirical evidence: 1) Studies across cities or metropolitan areas that have and have not implemented these laws, using data from the Current Population Survey pooled over many years; and 2) Studies within particular cities, based on comparisons of covered and uncovered workers before and after the laws are passed. I conclude that living wage laws have modestly raised wage levels of low wage workers and have reduced their employment at covered firms, but that the magnitudes of both effects are likely quite small, given how few workers are usually covered by these ordinances.
urn:nbn:de:101:1-20081126407
Keywords: J38; 330; living wages; Mindestlohn; Wirkungsanalyse; Lohnniveau; Lohnstruktur; Beschäftigungseffekt; Städtischer Arbeitsmarkt; USA